2021
DOI: 10.1021/acs.chemmater.1c02180
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic Hydrogels with a High Transmission Polymer Network for Pollutant Remediation

Abstract: Efficient heterogeneous and metal-free photocatalysts have recently been targeted as reusable materials for pollutant remediation. However, poor light penetration into photocatalytic materials currently limits modern photocatalytic systems due to uneven performance across the photocatalytic material and inefficient light usage. Here, we present a classical photocatalytic polymer hydrogel composed of a high transmittance polymer network and small conjugated photocatalytic moieties. Radical copolymerization of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 72 publications
2
25
0
5
Order By: Relevance
“…23−26 Homogeneous, nanoscale distributions of photocatalysts within polymersomes, 25 micelles, 26 nanoparticles, 27 and on surfaces 28 were reported, but the desired implementation of selectivity concepts into these structures is still a subject of on-going research. 23,24,29 Its versatility has already been demonstrated in a variety of chemical reactions such as water splitting, 30,31 CO 2 reduction, 32,33 organic pollutant degradation, 34 C−C coupling reactions, 35−37 C�C bond cleavage, 38−40 metal reduction, 41 oxidative coupling of amines, 42 trifluoromethylation of arenes, 43 oxidation of sulfides, 42 free radical polymerizations, 44−46 dehalogenation of halo ketones, 47 photodynamic therapy, 48−50 heterocycle formation, 51 bacterial treatment, 52 and enantioselective alpha-alkylation. 53 However, the scope in selectivity has been limited to date with restricted control given by the structural properties of the photocatalyst.…”
Section: ■ Introductionmentioning
confidence: 99%
“…23−26 Homogeneous, nanoscale distributions of photocatalysts within polymersomes, 25 micelles, 26 nanoparticles, 27 and on surfaces 28 were reported, but the desired implementation of selectivity concepts into these structures is still a subject of on-going research. 23,24,29 Its versatility has already been demonstrated in a variety of chemical reactions such as water splitting, 30,31 CO 2 reduction, 32,33 organic pollutant degradation, 34 C−C coupling reactions, 35−37 C�C bond cleavage, 38−40 metal reduction, 41 oxidative coupling of amines, 42 trifluoromethylation of arenes, 43 oxidation of sulfides, 42 free radical polymerizations, 44−46 dehalogenation of halo ketones, 47 photodynamic therapy, 48−50 heterocycle formation, 51 bacterial treatment, 52 and enantioselective alpha-alkylation. 53 However, the scope in selectivity has been limited to date with restricted control given by the structural properties of the photocatalyst.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Since we have briefly referenced the importance of light accessibility in photobased applications, a recent study showed the remarkable impact of highly transparent matrix obtained via DMAA-based hydrogel, which, when further cross-linked with benzothiadiazole and employed in the photo-oxidation of glyphosate ( N -(phosphonomethyl)­glycine)), RhB dye, organic sulfurs, and photoreduction of Cr VI . The overall results were all successful, clearly highlighting the importance of light penetration into hydrogel matrix to maximize light–semiconductor contact …”
Section: Hydrogelsmentioning
confidence: 82%
“…The overall results were all successful, clearly highlighting the importance of light penetration into hydrogel matrix to maximize light−semiconductor contact. 95 Hydrophobic association hydrogels (HyA) are the type of hydrogel that are built on hydrophobic interactions. This physical cross-linking intrinsically endowed high mechanical properties as well as effective self-healing properties to the final material.…”
Section: ■ Hydrogelsmentioning
confidence: 99%
“…7 Their advantages include precise control of conjugation lengths, cost-effectiveness, chemical robustness, and variability of properties through facile synthesis and direct access to the toolbox of classical polymer chemistry. 8,9 A few studies undertaken to date showed their promising potentials in synthesis and photocatalytic applications but barely included systematic investigations of structure−property relationships. 10−12 In particular, the effect of monomer composition remains unclear.…”
Section: ■ Introductionmentioning
confidence: 99%
“…They combine polymeric materials and photoactive small molecule properties by incorporating the latter as repeating units in a polymer backbone . Their advantages include precise control of conjugation lengths, cost-effectiveness, chemical robustness, and variability of properties through facile synthesis and direct access to the toolbox of classical polymer chemistry. , A few studies undertaken to date showed their promising potentials in synthesis and photocatalytic applications but barely included systematic investigations of structure–property relationships. In particular, the effect of monomer composition remains unclear. Such insights are essential to broaden understanding and address the key challenge of designing photoactive classical polymer materials in the future.…”
Section: Introductionmentioning
confidence: 99%